Analisis Kemampuan Pemecahan Masalah Matematika Melalui Tugas Proyek pada Materi Bilangan Bulat di SMP Negeri 1 Limboto - Isnarianti Sumba; Abdul Djabar Mohidin; Siti Zakiyah (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
This research is a quantitative descriptive study that aims to describe students' mathematical problem-solving abilities through project assignments on integer material. This research was conducted at SMP Negeri 1 Limboto in the even semester of the 2021/2022 academic year. The subjects in this study were class VII students, totalling 26 students. Data collection was obtained from test results in the form of project assignments and interviews were conducted to add to the information obtained. The results showed that the average achievement for students' abilities in completing project assignments was still moderate, namely 70%. This is indicated by the achievement of indicators understanding the problem by 90%, indicators planning a solution by 72%, indicators solving problems by 62% and indicators re-examining the results obtained by 52%.